Computer analysis of a crane subjected to moving point load - Piseth, Van. (2009)
This project investigates computer analysis of a crane subjected to moving point load and the difference between static and dynamic response of a crane. A modeling technique connects engineering software GT STRUDL to moving point load problem in dynamic analysis of a structure. Moving load problem is greatly influenced by critical speed concept. It exhibits high vibration level if load is moving at or near its critical speed. Critical speed of beam refers to the speed that induces maximum deflection. To implement the technique, a beam is divided into several equal segments by a number of nodes. The technique yields 1% error when a 6m beam is divided into 10 equal segments. The accuracy depends on time step and number of segments. It is found that the maximum dynamic vertical deflection is 1.158 times the static value when load move at critical speed in frame structure compared to ratio of 1.732 in beam theory. The beams that support moving loads in frame are called top beams. These top beams are allowed to move in vertical, horizontal and lateral directions. These boundary conditions significantly reduce the value of dynamic vertical deflection. The maximum deflection ratios are 1, 1.158 and 1.768 times compared to maximum static deflection when load move at normal operating speed 0.5m/s, critical speed 13.89m/s and four times value of critical speed 55.57m/s respectively.